Authority Of The Constitutional Court In Impeachment Of The President And/Or The Vice President According To The Basic Law Of The Republic Of Indonesia Of 1945 - Yulianto, Winasis; Silvana Amalia, Dyah (International Journal of Educational Research & Social Sciences, 2024)
One of the important results of the third amendment to the Republic of Indonesia Constitution of 1945 was the impeachment of the President and/or Vice President. Prior to the third amendment to the Republic of Indonesia Constitution of 1945, there was not a single article that regulated the impeachment of the President and/or Vice President. Even though the third amendment has passed 23 years, we have never had the experience of judicial impeachment in constitutional life in Indonesia. The three presidential impeachments that have occurred in Indonesia were not judicial impeachments, but political impeachments. President Sukarno, President Suharto and President Abdurrahman Wahid were impeached but did not use legal mechanisms through the Constitutional Court. This writing will raise two legal issues: first, whether the terms contained in the 1945 Constitution of the Republic of Indonesia, dismissal and dismissal, are appropriate according to Indonesian Law. Second, what is the mechanism for dismissing the President according to the 1945 Constitution of the Republic of Indonesia after the amendment. The method used in this research is normative juridical research. The approaches used in this research are the statutory approach, conceptual approach, historical approach, case approach and comparative legal approach. From the discussion in this article, it can be concluded that the words "dismissal" and "dismissed" are not appropriate. This is based on the idea that "dismissal" and "dismissed" are not legal language. Thus, according to Indonesian law, it needs to be changed with the word "Pemakzulan" for the word "dismissal" and the word "impeached" for the word "dismissed". The impeachment procedure begins with the DPR's opinion that the President and/or Vice President has committed treason against the state, corruption, bribery, other serious criminal acts or disgraceful acts and/or is proven to be ineligible as president and/or Vice President. The DPR's opinion is registered with the Constitutional Court, with the requirement that 2/3 of the DPR members must be present and 2/3 of the DPR members present support the DPR's opinion. If the Constitutional Court decides that the President and/or Vice President have been proven to have violated the law, the DPR holds a plenary session to forward the proposal to dismiss the President and/or Vice President to the MPR. No later than 30 days after the MPR receives the proposal, the MPR is obliged to hold a session to decide on the DPR's proposal. The MPR's decision on the DPR's proposal must be taken at an MPR plenary meeting attended by ¾ of the members and approved by 2/3 of the total MPR members present.